The Efficacy and Safety of Superficial Chemical Peel in the Treatment of Plane Wart - Ayhan Omar Abdulkareem; Ali M. D hahir Elethawi (Advanced Medical Journal)
Background and objectives: Treatment of plane warts is problematic, methods such as cryotherapy and cauterization is associated with high recurrence rate beside the risk of scar, pain and high cost. The aim of this study is to assess the effectiveness and safety of salicylic acid 30% superficial chemical peels in comparison with glycolic acid 70% solution in treatment of Plane wart.